2017
DOI: 10.1007/s10456-017-9559-4
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of physiological interstitial flow eliminate morphogen gradients and guide angiogenesis

Abstract: Convective transport can significantly distort spatial concentration gradients. Interstitial flow is ubiquitous throughout living tissue, but our understanding of how interstitial flow affects concentration gradients in biological processes is limited. Interstitial flow is of particular interest for angiogenesis because pathological and physiological angiogenesis is associated with altered interstitial flow, and both interstitial flow and morphogen gradients (e.g., vascular endothelial growth factor, VEGF) can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
97
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(109 citation statements)
references
References 52 publications
12
97
0
Order By: Relevance
“…Together, these results suggest that biomolecular factors and interstitial flow cooperate in guiding lymphangiogenesis. It is noteworthy that the outcome described by Kim et al is similar to what was previously reported with the application of microfluidic systems on the directional bias of blood vessel angiogenesis when interstitial flow is oriented against the direction of sprouting …”
Section: Microfluidic Approaches For Studying Lymphatic Vasculaturesupporting
confidence: 83%
“…Together, these results suggest that biomolecular factors and interstitial flow cooperate in guiding lymphangiogenesis. It is noteworthy that the outcome described by Kim et al is similar to what was previously reported with the application of microfluidic systems on the directional bias of blood vessel angiogenesis when interstitial flow is oriented against the direction of sprouting …”
Section: Microfluidic Approaches For Studying Lymphatic Vasculaturesupporting
confidence: 83%
“…For both computations, time grows from left to right. The results show that our model predicts more prominent growth of the neovasculature against the flow, as observed in a recent experiment [18]. The VEGF was kept constant on the lateral boundaries with concentration f ¼ f HYC .…”
Section: The Neovasculature Grows More Prominently Against the Flowsupporting
confidence: 85%
“…Interface 15: 20180415 uniform flow in horizontal direction is applied. When a controlled interstitial flow is applied, the experiments show a strikingly non-symmetric distribution of the neovasculature, while similar experiments without flow produce symmetric growth; see [18] for more details. The detailed mechanisms that control the symmetry breaking are not well understood.…”
Section: The Neovasculature Grows More Prominently Against the Flowmentioning
confidence: 85%
See 1 more Smart Citation
“…The VMO platform is fabricated from polydimethylsiloxane (PDMS), an optically clear, biologically inert polymer widely used in the microfluidics field [91]. The use of this polymer and the dimensions of the platform ensure that live, GFP-transduced endothelial progenitor cells (ECFC-EC) can be imaged and quantified throughout vessel formation.…”
Section: 3d Models Of Vascular Morphogenesismentioning
confidence: 99%